ANALISIS BIAYA DAN PENDAPATAN USAHATANI JAGUNG MANIS (Zea mays saccharata sturt) DI KELURAHAN LOKTABAT UTARA KECAMATAN BANJARBARU UTARA - Zulipah Mahdalena; Yayuk Minta Wahyuningsih; Ahmad Baparki (Chlorophyl, 2022)
This study aimed to determine the costs, production,revenue, and income of sweet corn in Loktabat utara village, Banjarbaru utara district. The method used in the reasearch is survey and observation method. . The sampling technique used purposive sampling method, so that 9 respondents were obtained. The results of this study showed that the average production of sweet corns in the loktabat utara village was 7.089 cobs/farmer or 6.262 kg/Ha. The everage explicit cost is Rp.1.236.856/ farmer. While The average revenue obtained is Rp.10.633.000/farmer. The everage income earned during one production process is Rp.9.379.000/farmer